KONSEP HUMANISME BERBASIS NILAI MODERASI BERAGAMA: ANALISIS SURAT AL-BAQARAH AYAT 143 - nurhasanah, muwahidah; Jabar Idharudin, Abdul; Sumarno (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This research involves support from various extreme religious groups, both from the left and right. This phenomenon can be understood as a concept related to radicalism on one side and liberalism on the other. Extremism in this context is not limited to Islam and Islamism, but also encompasses characteristics of Islam as outlined in the Qur'an, referred to as Islam wasathan. The application of a moderate stance is in line with the teachings in Q.S. al-Baqarah verse 143, although it should be noted from the outset that this statement is not entirely accurate. To realize moderation or wasathiyah as a guideline for thinking, behaving, and acting for Muslims, preliminary steps are necessary. This research aims to analyze several issues: (1) What does Q.S. al-Baqarah verse 143 explain about social moderation in religious practice? (2) How can the concept of moderation be applied according to Surat Al-Baqarah:143? This study also investigates whether this support comes from highly esoteric religious groups. Furthermore, the application of moderation principles aligns with the goals of Islamic education, emphasizing the importance of openness; Q.S. al-Baqarah verse 143 asserts that an educator must be able to adopt an open attitude and provide guidance in the process of teaching Islam. The method of Islamic education is based on compassion, prioritizing polite and open attitudes in the learning environment. It is hoped that the results of this research can contribute to the development of knowledge among academics as well as educators and parents in their efforts to moderate students' understanding in daily life.